Back to the moon - Travis S Taylor; Les Johnson (Distributed by Simon & Schuster, 2010)
As a U.S. mission to the Moon prepares to lift off decades after the 1969 lunar mission, a secret Chinese trip to the Moon is revealed when a distress signal is received, prompting the U.S. team to turn a journey of discovery into a desperate rescue mission.